НЕПРОБОЈНИ ЗИД ЋУТАЊА УПРАВЕ У СРБИЈИ - Cucić, Vuk (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The administrative silence, as an apparent manifestation of maladministration, becomes an ever increasing problem in Serbia. The number of lawsuits against administrative silence submitted to the Administrative Court increased more than 26 times in the last 10 years.Two potential reasons why the parties do not submit administrative appeals and lawsuits to the Administrative Court against administrative silence even more often could be the lack of necessary legal knowledge (most of the parties are lay persons) or their distrust in the available legal protection mechanisms.Unfortunately, the legislator and the judiciary have undertaken measures that further aggravate the situation. This paper discusses two forms of legislative and judicial support to administrative silence, which discourage parties from using legal remedies against administrative silence and refrain them from engaging lawyers.The legislator effectively supports administrative silence by, safe for one exception, preventing parties from claiming damages for the damage they sustained due to the failure of competent administrative authorities to decide in their cases in a timely manner. The Administrative Court supports the administrative silence by a legal stand prescribing that a party is not entitled to reimbursement of the costs of the proceedings, including the costs of lawyer’s services, provided that the first-instance administrative authority replaced its act challenged by an administrative appeal before the Administrative Court decided on the lawsuit against administrative silence.